Ten Years of Strategic Collaboration of Libraries in Digital Preservation - Zarnitz, Monika; Bähr, Thomas; Arning, Ursula (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2019)
The German National Specialist Libraries cooperate closely in the field of digital preservation. One of the partners hosts the preservation system, while each library creates its own workflows and is free to ingest its digital material into this system. This paper delineates the factors for success of this collaboration. It describes the different aspects of collaboration in digital preservation and describes the benefits and costs of cooperation in this field as a case study.Digital preservation is resource intensive and the required technology is complex. Therefore the libraries benefit from synergy effects: Reduced cost by sharing the preservation system, usage of similar workflows and formats of digital objects, work sharing in networking activities and staff training. The paper also stresses the advantages and difficulties while applying for certificates in a consortium. Their collaboration extends to intensive national and international networking activities, which yield more contacts than a single library could maintain if it acted on its own. The libraries’ staffs are active in working groups of nestor – the German network for digital preservation – and in working groups of the Open Preservation Foundation.